Regulated Necrosis Orchestrates Microglial Cell Death in Manganese-Induced Toxicity. (21st November 2018) - Porte Alcon, Soledad; Gorojod, Roxana Mayra; Kotler, Mónica Lidia
Graphical abstract: Highlights: Mn triggers regulated necrosis by parthanatos and lysosomal disruption in BV-2 cells. Mn exposure leads to reactive oxygen species (ROS) generation and DNA damage. Mn induces mitochondrial membrane permeabilization and AIF nuclear translocation. Mn triggers cathepsin (Cat) release from lysosomes. PARP-1 and Cat activities are required for Mn-induced microglial cell death. Abstract: Microglia, the brain resident immune cells, play prominent roles in immune surveillance, tissue repair and neural regeneration. Despite these pro-survival actions, the relevance of these cells in the progression of several neuropathologies has been established. In the context of manganese (Mn) overexposure, it has been proposed that microglial activation contributes to enhance the neurotoxicity. However, the occurrence of a direct cytotoxic effect of Mn on microglial cells remains controversial. In the present work, we investigated the potential vulnerability of immortalized mouse microglial cells (BV-2) toward Mn 2+, focusing on the signaling pathways involved in cell death. Evidence obtained showed that Mn 2+ induces a decrease in cell viability which is associated with reactive oxygen species (ROS) generation. In this report we demonstrated, for the first time, that Mn 2+ triggers regulated necrosis (RN) in BV-2 cells involving two central mechanisms: parthanatos and lysosomal disruption. The occurrence of parthanatos is supported by several cellular and molecular events: (i) DNA damage; (ii) AIF translocation from mitochondria to the nucleus; (iii) mitochondrial membrane permeabilization; and (iv) PARP1-dependent cell death. On the other hand, Mn 2+ induces lysosomal membrane permeabilization (LMP) and cathepsin D (CatD) release into the cytosol supporting the lysosomal disruption. Pre-incubation with CatB and D inhibitors partially prevented the Mn 2+ -induced cell viability decrease. Altogether these events point to lysosomes as players in the execution of RN. In summary, our results suggest that microglial cells could be direct targets of Mn 2+ damage. In this scenario, Mn 2+ triggers cell death involving RN pathways.